5.27.5 Problems 401 to 500

Table 5.1175: Second order, Linear, non-homogeneous and constant coefficients

#

ODE

Mathematica

Maple

3798

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 4 \,{\mathrm e}^{-2 x} \]

3802

\[ {}y^{\prime \prime }-4 y = 5 \,{\mathrm e}^{x} \]

3803

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 2 x \,{\mathrm e}^{-x} \]

3804

\[ {}y^{\prime \prime }-y = 4 \,{\mathrm e}^{x} \]

3806

\[ {}y^{\prime \prime }+4 y = \ln \left (x \right ) \]

3807

\[ {}y^{\prime \prime }+2 y^{\prime }-3 y = 5 \,{\mathrm e}^{x} \]

3808

\[ {}y^{\prime \prime }+y = \tan \left (x \right ) \]

3809

\[ {}y^{\prime \prime }+y = 4 \cos \left (2 x \right )+3 \,{\mathrm e}^{x} \]

3937

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 4 \]

3938

\[ {}y^{\prime \prime }-y^{\prime }-12 y = 36 \]

3939

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 10 \,{\mathrm e}^{-t} \]

3940

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 4 \,{\mathrm e}^{3 t} \]

3941

\[ {}y^{\prime \prime }-2 y^{\prime } = 30 \,{\mathrm e}^{-3 t} \]

3942

\[ {}y^{\prime \prime }-y = 12 \,{\mathrm e}^{2 t} \]

3943

\[ {}y^{\prime \prime }+4 y = 10 \,{\mathrm e}^{-t} \]

3944

\[ {}y^{\prime \prime }-y^{\prime }-6 y = 12-6 \,{\mathrm e}^{t} \]

3945

\[ {}y^{\prime \prime }-y = 6 \cos \left (t \right ) \]

3946

\[ {}y^{\prime \prime }-9 y = 13 \sin \left (2 t \right ) \]

3947

\[ {}y^{\prime \prime }-y = 8 \sin \left (t \right )-6 \cos \left (t \right ) \]

3948

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 10 \cos \left (t \right ) \]

3949

\[ {}y^{\prime \prime }+5 y^{\prime }+4 y = 20 \sin \left (2 t \right ) \]

3950

\[ {}y^{\prime \prime }+5 y^{\prime }+4 y = 20 \sin \left (2 t \right ) \]

3951

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 3 \cos \left (t \right )+\sin \left (t \right ) \]

3952

\[ {}y^{\prime \prime }+4 y = 9 \sin \left (t \right ) \]

3953

\[ {}y^{\prime \prime }+y = 6 \cos \left (2 t \right ) \]

3954

\[ {}y^{\prime \prime }+9 y = 7 \sin \left (4 t \right )+14 \cos \left (4 t \right ) \]

3963

\[ {}y^{\prime \prime }-y = \operatorname {Heaviside}\left (t -1\right ) \]

3964

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 1-3 \operatorname {Heaviside}\left (t -2\right ) \]

3965

\[ {}y^{\prime \prime }-4 y = \operatorname {Heaviside}\left (t -1\right )-\operatorname {Heaviside}\left (t -2\right ) \]

3966

\[ {}y^{\prime \prime }+y = t -\operatorname {Heaviside}\left (t -1\right ) \left (t -1\right ) \]

3967

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = -10 \operatorname {Heaviside}\left (t -\frac {\pi }{4}\right ) \cos \left (t +\frac {\pi }{4}\right ) \]

3968

\[ {}y^{\prime \prime }+y^{\prime }-6 y = 30 \operatorname {Heaviside}\left (t -1\right ) {\mathrm e}^{1-t} \]

3969

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 5 \operatorname {Heaviside}\left (t -3\right ) \]

3970

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = 2 \sin \left (t \right )+\operatorname {Heaviside}\left (t -\frac {\pi }{2}\right ) \left (1+\cos \left (t \right )\right ) \]

3977

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = \delta \left (t -1\right ) \]

3978

\[ {}y^{\prime \prime }-4 y = \delta \left (t -3\right ) \]

3979

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = \delta \left (t -\frac {\pi }{2}\right ) \]

3980

\[ {}y^{\prime \prime }-4 y^{\prime }+13 y = \delta \left (t -\frac {\pi }{4}\right ) \]

3981

\[ {}y^{\prime \prime }+4 y^{\prime }+3 y = \delta \left (t -2\right ) \]

3982

\[ {}y^{\prime \prime }+6 y^{\prime }+13 y = \delta \left (t -\frac {\pi }{4}\right ) \]

3983

\[ {}y^{\prime \prime }+9 y = 15 \sin \left (2 t \right )+\delta \left (t -\frac {\pi }{6}\right ) \]

3984

\[ {}y^{\prime \prime }+16 y = 4 \cos \left (3 t \right )+\delta \left (t -\frac {\pi }{3}\right ) \]

3985

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 4 \sin \left (t \right )+\delta \left (t -\frac {\pi }{6}\right ) \]

4129

\[ {}y^{\prime \prime }-4 y^{\prime }+3 y = 1 \]

4130

\[ {}y^{\prime \prime }+y^{\prime }-2 y = -2 x^{2}+2 x +2 \]

4131

\[ {}y^{\prime \prime }+y = x^{3}+x \]

4132

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = {\mathrm e}^{2 x} \]

4133

\[ {}y^{\prime \prime }+2 y = x +{\mathrm e}^{2 x} \]

4134

\[ {}y^{\prime \prime }+2 y = {\mathrm e}^{x}+2 \]

4135

\[ {}y^{\prime \prime }-y = 2 \,{\mathrm e}^{x} \]

4136

\[ {}y^{\prime \prime }+y = \sin \left (x \right ) \]

4137

\[ {}y^{\prime \prime }-y = 4 x \,{\mathrm e}^{x} \]

4138

\[ {}y^{\prime \prime }-2 y^{\prime }+3 y = x^{3}+\sin \left (x \right ) \]

4141

\[ {}y^{\prime \prime }+2 n y^{\prime }+n^{2} y = A \cos \left (p x \right ) \]

4152

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = \sin \left (x \right ) \]

4153

\[ {}y^{\prime \prime }+2 y^{\prime }-2 y = x^{2}+1 \]

4154

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{2}+\frac {y}{8} = \frac {\sin \left (x \right )}{8}-\frac {\cos \left (x \right )}{4} \]

4155

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = {\mathrm e}^{x}-2 \,{\mathrm e}^{2 x}+\sin \left (x \right ) \]

4156

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = x^{3} {\mathrm e}^{2 x}+{\mathrm e}^{2 x} x \]

4157

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = \sin \left (2 x \right ) x \]

4158

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = {\mathrm e}^{x} \sin \left (x \right ) \]

4162

\[ {}y^{\prime \prime }+9 y = 8 \sin \left (x \right ) \]

4164

\[ {}9 y^{\prime \prime }-6 y^{\prime }+y = \left (4 x^{2}+24 x +18\right ) {\mathrm e}^{x} \]

4456

\[ {}y^{\prime \prime }+6 y^{\prime }+10 y = 3 x \,{\mathrm e}^{-3 x}-2 \,{\mathrm e}^{3 x} \cos \left (x \right ) \]

4457

\[ {}y^{\prime \prime }-8 y^{\prime }+17 y = {\mathrm e}^{4 x} \left (x^{2}-3 x \sin \left (x \right )\right ) \]

4458

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = \left (x +{\mathrm e}^{x}\right ) \sin \left (x \right ) \]

4459

\[ {}y^{\prime \prime }+4 y = \sinh \left (x \right ) \sin \left (2 x \right ) \]

4460

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = \cosh \left (x \right ) \sin \left (x \right ) \]

4470

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 36 \,{\mathrm e}^{2 x} x \]

4474

\[ {}y^{\prime \prime }+3 y^{\prime }+5 y = 5 \,{\mathrm e}^{-x} \sin \left (2 x \right ) \]

4476

\[ {}y^{\prime \prime }+4 y = 8 \sin \left (x \right )^{2} \]

4479

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = \left (1+x \right ) {\mathrm e}^{x}+2 \,{\mathrm e}^{2 x}+3 \,{\mathrm e}^{3 x} \]

4480

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = 4 \,{\mathrm e}^{x} \cos \left (2 x \right ) \]

4481

\[ {}y^{\prime \prime }+4 y = 4 \sin \left (2 x \right ) \]

4482

\[ {}y^{\prime \prime }-y = 12 \,{\mathrm e}^{x} x^{2}+3 \,{\mathrm e}^{2 x}+10 \cos \left (3 x \right ) \]

4483

\[ {}y^{\prime \prime }+y = 2 \sin \left (x \right )-3 \cos \left (2 x \right ) \]

4484

\[ {}y^{\prime \prime }-y^{\prime } = {\mathrm e}^{x} \left (x^{2}+10\right ) \]

4485

\[ {}y^{\prime \prime }-4 y = 96 x^{2} {\mathrm e}^{2 x}+4 \,{\mathrm e}^{-2 x} \]

4486

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = 5 \cos \left (x \right )+10 \sin \left (2 x \right ) \]

4487

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = 4 x -2+2 \,{\mathrm e}^{x} \sin \left (x \right ) \]

4488

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 4 x \,{\mathrm e}^{2 x} \sin \left (2 x \right ) \]

4497

\[ {}y^{\prime \prime }-y = \frac {1}{x}-\frac {2}{x^{3}} \]

4498

\[ {}y^{\prime \prime }-y = \frac {1}{\sinh \left (x \right )} \]

4499

\[ {}y^{\prime \prime }-2 y^{\prime }+y = \frac {{\mathrm e}^{x}}{x} \]

4500

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = \sin \left ({\mathrm e}^{x}\right ) \]

4501

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = \sin \left ({\mathrm e}^{-x}\right ) \]

4502

\[ {}y^{\prime \prime }+y = \sec \left (x \right )^{3} \]

4503

\[ {}y^{\prime \prime }-y = \frac {1}{\sqrt {1-{\mathrm e}^{2 x}}} \]

4504

\[ {}y^{\prime \prime }-y = {\mathrm e}^{-2 x} \sin \left ({\mathrm e}^{-x}\right ) \]

4505

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 15 \,{\mathrm e}^{-x} \sqrt {1+x} \]

4506

\[ {}y^{\prime \prime }+4 y = 2 \tan \left (x \right ) \]

4507

\[ {}y^{\prime \prime }-2 y^{\prime }+y = \frac {{\mathrm e}^{2 x}}{\left (1+{\mathrm e}^{x}\right )^{2}} \]

4508

\[ {}y^{\prime \prime }+y^{\prime } = \frac {1}{1+{\mathrm e}^{x}} \]

4514

\[ {}y^{\prime \prime }+4 y^{\prime }+3 y = 60 \cos \left (3 t \right ) \]

4515

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 9 \,{\mathrm e}^{-2 t} \]

4516

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 2 t^{2}+1 \]

4517

\[ {}y^{\prime \prime }+4 y = 8 \sin \left (2 t \right ) \]

4518

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 4 \,{\mathrm e}^{-t}+2 \,{\mathrm e}^{t} \]

4519

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = 8 \sin \left (t \right ) {\mathrm e}^{-t} \]

4520

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = 8 \,{\mathrm e}^{t} \sin \left (2 t \right ) \]